Adaptive capacity to climate change: A synthesis of concepts, methods, and findings in a fragmented field. (3rd January 2019) - Siders, A.R.
Abstract : Adaptive capacity is an important element of long‐term adaptation to climate change and is the focus of a rapidly growing body of research. Interdisciplinary growth has the potential to introduce new methods and insights, but it could also cause fragmentation and hamper methodological development or limit transfer of academic insights to climate change adaptation practice. This article uses qualitative content, bibliometric, and citation network analyses to systematically review the scope, methods, and findings of 276 studies on adaptive capacity of social and social‐ecological systems. The review demonstrates that adaptive capacity research is highly interdisciplinary; covers a wide range of sectors, geographic locations, and scales of analysis; and is highly fragmented. The majority of empirical studies are isolated by lack of comparative work and cross‐field citation. Forty‐six percent of studies reviewed do not cite prior works on adaptive capacity: even those on similar topics in the same geographic location. Methods to assess adaptive capacity have proliferated to include more than 64 indicator‐based indices or frameworks and 37 proxy outcome measures. The article argues that lack of either consensus or debate across the literature raises concerns that scientific progress in the field may be constrained and the ability of adaptive capacity research to inform adaptation practice may be limited. To promote consistency and transparency in future work, 158 determinants of adaptive capacity are defined and illustrated with common assessment indicators and examples. Additional opportunities for progress are noted with suggestions for future research. This article is categorized under: Vulnerability and Adaptation to Climate Change > Institutions for Adaptation Abstract : Adaptive capacity to climate change research is a growing interdisciplinary field, but lack of cross‐field citation may be leading to conceptual and methodological fragmentation. Over 100 methods to assess adaptive capacity exist. A concept and indicator database is proposed to promote consistency in future work.